(untitled) (Al-Aasar, 2025)
The Holy Qurān is the final, unalterable, and comprehensive Waḥi (revelation) from Allah, serving as a source of guidance until the Day of Resurrection. Its universality and inclusivity, its multidimensional and all-encompassing nature, necessitate that the purposes of its Waḥi (revelation)be clearly defined. In response to this requirement, the guides of humanity in every age have endeavored to delineate its objectives from their respective perspectives. The views of numerous scholars shed light upon these purposes from diverse angles. Each authority in the field, according to his intellectual capacity and personal inclination, has employed and formulated distinct terminologies. Yet, in their discourse on the objectives of the Qur’an, the dimension consistently regarded as indispensable by these scholars has been spiritual elevation: the Tazkiyyah (purification of the heart), Taṣfiyyah (the illumination of the soul), Iklhaṣ (sincerity in worship), submission to the Supreme and Exalted Lord, the attainment of His pleasure, ultimately and the love of Beloved. The general and widely recognized term by which all of these dimensions are commonly expressed and understood is taṣawwuf.